Analisis Sistem Proteksi Kebakaran dan Keselamatan Kebakaran di Stasiun Transit Manggarai Kereta Rel Listrik (KRL) Commuter Line Jabodetabek Tahun 2023 - Achmad, Naila Adinda; Hendra, Hendra (UI Scholars Hub, 2023)
Stasiun Manggarai is the most active station. In January 2023, Stasiun Manggarai has 150,000 transit users and 14,000 station users per day (Fransisca, 2023). This large number of users can certainly increase the density – and according to research – density can increase the existing potential hazards and risks, including fire hazards. Therefore, this research was conducted to find out the implementation of fire protection and fire safety system at Stasiun Transit Manggarai Kereta Rel Listrik (KRL) Commuter Line Jabodetabek using a descriptive observational method with comparative approach. The author compares the results of implementing fire protection and fire safety systems at Manggarai Station with NFPA 130 and Code of Practice for Fire Precautions in Rapid Transit Systems 2022. The results of this study were obtained through interviews, document review, and observation. The research found that the proportion of implementation of fire protection and fire safety systems at the Stasiun Manggarai is 84.34% with the highest fulfillment at the percentage of 100% on Function, Reliability, and Availability of Communication and Control Systems; and Wire and Cable Requirements aspect. The lowest compliance is in the Emergency Communication System aspect with the percentage of 50%.